STRATEGI INOVATIF MTS AZIZAN PALEMBANG: MENERAPKAN ETIKA BERSOSIAL MEDIA DALAM PENDIDIKAN AQIDAH AKHLAK MELALUI METODE CERAMAH DAN TANYA JAWAB - Serhli Adellia; Siti Holijah; Linda Agustin; Muhammad Riswanda; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research investigates the methods of teaching social media ethics at MTS Azizan Palembang. Data were collected using two approaches, namely lectures and question-and-answer sessions. In the qualitative approach, information was obtained through observation, in-depth interviews, and document analysis. The research participants included teachers and students involved in the learning of Islamic religious education. The results indicate that the lecture method is effective in conveying the basic principles of social media ethics, while the question-and-answer sessions encourage active interaction and critical reflection from students. The combination of these two methods helps to strengthen students' understanding of the importance of ethical behavior on social media.